Robotic-Assisted Pelvic Reconstruction After Metastatic Renal Cell Carcinoma Resection: A Case Report. Issue 4 (October 2021) - Ameri, Bijan Joseph; O'Keefe, Shawn; Lima, Diego; Higuera-Rueda, Carlos; Manrique, Jorge
Abstract : Case: A 76-year-old man presented with metastatic renal cell carcinoma (RCC) in the right acetabulum with pelvic compromise. The patient had right hip pain and difficulty with ambulation, as such he elected to undergo tumor resection with subsequent reconstruction of pelvic defect. Given the size and location of the anticipated pelvic defect, robotic-assisted hip arthroplasty was used to execute prosthetic component placement and anatomic pelvic reconstruction. Conclusion: Advances in technology, such as robotics and 3D navigation, have application in orthopaedic oncology surgery, especially for reconstructions after pelvic resections. The goal of this case report is to describe the utility of this technology in a case of metastatic RCC.